DETERMINAN PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN SEKTOR PERBANKAN YANG TERCATAT DI BEI - Aprianto, Ryan; Desyana, Gita; Noviarty, Helisa (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
A study was conducted to exaimine how profitability, Leverage, firm size, and firm can influence the disclosure of corporate social responsibility . The study employed a quantitative design, utilizing secondary data sourced from the annual reporst and sustainability reports of companies via the official website of the Indonesia Stock Exchange. The population of the study comprised banking sector companies listed on the IDX for the period of 2020-2023. A random sampling method was employed with purposive sampling, resulting in a size of 30 companies. Panel data regression analysis techniques will be used, along with Chow test and Hausman test to determine the regression analysis processed with the Eviews 12 software. The study found that profitability, Leverage, and firm age did not significantly effect CSR disclosure. Conversely, firm size showed a positive and significant influence on CSR disclosure.